Assessment of gestational age using anthropometric parameters in newborns - Asokan, Bharathi; Saravanan S. (International Journal of Contemporary Pediatrics, 2023)
Background: Estimation of gestational age was needed for the measurement of intrauterine growth and associated conditions, such as whether infants with a low birth weight are preterm or growth-retarded, and identifying high-risk status for developmental delay. Menstrual history was unreliable in most of the cases and ultrasound was not feasible in low resource area, so in this study we were used anthropometric measurements as a simple tool for assessment of gestational age. Methods: This study was a cross sectional observational study conducted in 380 babies born in January 2020-December 2022 in department of pediatrics, Rajah Muthiah Medical College and Hospital. The data were collected using semi-structured questionnaire and anthropometric assessment. The Epi info 7 software was used to analyse the data. Results: The mean gestational age among neonates studied was 37.06±2.32 weeks, the mean head circumference was 33.48±1.01 cm and majority of them 141 babies had head circumference 33 cm, the mean chest circumference was 30.69±1.08 cm. and majority of the babies, had chest circumference of 30 cm, the mean foot length was 7.64±0.24 cm, the mean length of the babies was 47.9±1.26 cm. Conclusions: Our study conclude that anthropometeric parameters in combination (head, chest circumference, length, foot length, birth weight) and as single parameters (foot length) was a simple and easy tool for assessing gestational age in low resource setting where we can make quick referral.